Causal effects of homocysteine levels on the components of sarcopenia: A two-sample mendelian randomization study - Yu, Hongwei; Luo, Gan; Sun, Tianwei; Tang, Qiong (Frontiers in Genetics, 2022)
Abstract Background: Currently, it is unclear whether there is a causal association between genetically predicted plasma homocysteine (Hcy) levels and the risk of sarcopenia. We performed a Mendelian randomization (MR) study to assess the association between circulating Hcy levels and the components (grip strength, walking pace, and appendicular lean mass(ALM)) of sarcopenia. Methods: Independent single nucleotide polymorphisms (SNPs) significantly associated with plasma Hcy levels served as instrumental variables. Summary-level data regarding the components of sarcopenia were obtained from the UK Biobank. Inverse variance weighted (IVW) as the primary method was used for Mendelian randomization(MR) analysis. We also use four models, weighted median , MR-Egger regression, Maximum likelihood, and Penalised weighted median, as supplementary methods to IVW to test the stability of the results. The MR-Egger intercept test, Cochran’s Q test, and“leave-one-out” sensitivity analysis were performed to evaluate the horizontal pleiotropy, heterogeneities, and stability of the causal association between Hcy levels and the components of sarcopenia. Results: The IVW–MR analysis suggested significant negative associations of increased plasma Hcy levels with grip strength (right: effect=-0.036, SE=0.032, P=5.53E-4; left: effect=-0.045, SE=0.010, P=1.45E-5), walking pace (effect=-0.038, SE=0.011, P=3.18E-4), and ALM (effect=-0.058, 0.013, P=1.03E-5). However, there were no significant associations of decreased plasma Hcy levels with grip strength (right: effect=0.005, SE=0.021, P=0.82; left: effect=-0.006, SE=0.014, P=0.64), walking pace (effect=0.01, 0.020, P=0.61), or ALM (effect=-0.034, SE=0.018, P=0.06).The accuracy and robustness of these findings were confirmed by sensitivity tests. Conclusions: Increased circulating Hcy levels were associated with lower grip strength, slower walking pace, and decreased ALM. Keywords: Homocysteine, grip strength, walking pace, appendicular lean mass, Mendelian randomization.